Effect of Quality Service Delivery on Customer Satisfaction: The Case of Awash Bank in Nekemte District, Oromia, Ethiopia - Gadisa Teshome Chali (Amicus Curiae: Journal of Law and Justice Dialogue, 2025)
The banking industry of Ethiopia plays a crucial role in the country's economy. Like the financial institutions and service sectors, the activities of commercial banks mainly depend on customers. Therefore, the major objective of this study is to assess the effect of quality service delivery on customer satisfaction, as shown in the case of Awash Bank in Nekemte District. To attain this objective, a questionnaire was designed and categorized under the five dimensions of the Servequal model. The sample consists of 202 respondents selected based on a convenience sampling procedure. This study used a quantitative research design and both primary and secondary data. The collected data was analyzed with the help of SPSS version 24. Pearson Correlation analysis was used to assess the relationship between dependent and independent variables. The correlation results indicate that there is a positive correlation between the dimensions of service quality and customer satisfaction. The results of the regression test showed that offering quality service has a positive impact on overall customer satisfaction. The findings of the analysis showed that the performance of Awash Bank in Nekemte District in providing quality service is not in a position to meet the expectations of the customer. Low service quality leads to low customer satisfaction. Based on this, the researcher suggested that in order to improve the performance of the bank, Awash Bank should provide training to its customer service officers to provide individual attention to its customers. Improving the physical appearance and facilities of its branches should also be done to enhance the tangibility of its services. Further, periodic measurement of service quality and customer satisfaction should be practised.